Influence of Internal Control Measures on Business Operation Effeciency: A Case Study-Kenya Women Micro-Finance Bank - Opiyo, Maurice Lima (University of Embu, 2019)
Enhancing operation efficiency is one of the objectives of internal control systems (!CS). This study examines the relationship between !CS implementation and in achieving operational efficiency of Kenya Women Micro-Finance Bank, initially it was Kenya Women Finance Trust (KWFT). Therefore, the main objective of the study was to determine the effect of internal controls on the business operation efficiency. The study embraced descriptive research method. Management and employees of Kenya Women Microfinance Bank were the targeted population of the study which was 33 lin number with a sample size of 53 persons, where census was employed as implying techniques and purposive sampling technique in picking the respondents. Data collection was through interview program and questionnaire schedules. The findings revealed that effective operating control used in the organization at most is the adequate planning and coordination of activities as shown by 88.8 % of the total repondents. On the part of personnel controls ,88. 7% of the respondents were of the opinion that employees' recruitment policies and procedures are documented and followed to the latter. On the other hand, concerning to organizational controls, 92.5% of them said that financial controls are mostly used by the organization. Recommendations were; the organization should make internal controls part of risk management to reduce risks which are hidden to the management, they should also connect objectives of each and every person and promote goal congruent with employees and finally on and off the job training should be done even if skilled employee are recruited The study would be of great benefit to the industry and other firms in the related field since it would give understanding to them on the importance of incorporating internal control systems in their operations and how it would assist them in obtaining their obligations and operational efficiency in their areas of operations.